Banana Waste (Musa acuminata Cavendish Subgroup) as A Sources Eco-Feed for Ruminants in Lampung Province: Potential and Nutrient Content - ULVI FITRI HANDAYANI; BOBY ARYA PUTRA; AYU SRI ENDAYANI; A. RESHI DANU NARWASTU; REFKI SANJAYA (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
This research was conducted to determine the potential of banana waste (Musa acuminata Cavendish Subgroup), nutritional content, and phytochemical compounds. This study used descriptive analysis using interviews and field observations, as well as proximate analysis of the nutrient content i.e. whole banana, banana peel, and banana stem waste, and also phytochemical screening of banana peels and banana stems. Based on dry matter, whole banana waste contains 10.23% Ash, 1.80% Fat, 3.82% Crude Protein (CP), 8.81 Crude Fiber (CF), and 75.34% Nitrogen-Free Extract (NFE). Banana peel waste contains 6.33% Ash, 4.12% Fat, 4.67% CP, 18.46 CF, and 66.42% (NFE). Banana stem waste contains 25.84% Ash, 1.74% Fat, 11.64% CP, 41.88 CF, and 18.90% (NFE). Banana banana stems and peels contains flavonoids, tannins, saponins, and terpenoids but they does not contain alkaloids. Whole banana waste, or banana peel and banana stem waste, from the Cavendish banana species (Musa acuminata Cavendish Subgroup) has the potential to be used as animal feed ingredients, especially for ruminants. However, further research is needed for livestock or the processing of banana waste to be optimally utilized.